The cultural proficiency journey moving beyond ethical barriers toward profound school change - CampbellJones, Franklin; CampbellJones, Brenda; Lindsey, Randall B.; Sage eBooks (Thousand Oaks, Calif. : Corwin ; London : SAGE [distributor], 2010)
This text calls on educators to facilitate personal and systemic change that translates into responsible actions in a multicultural society. Using detailed case studies based on actual school events, it provides an understanding of cultural proficiency as an ethical and moralistic approach for profound organizational school change.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Multicultural education -- United States; School improvement programs -- United States; Educational leadership -- United States; Electronic books